STUDY OF PHENIBUT ANTIEDEMIC ACTION AND NEW GABA DERIVATIVES - T. N. Scherbakova; P. A. Ozerova (Фармация и фармакология (Пятигорск), 2015)
We have studied phenibut, gammalone, and new GABA derivatives action on the development of experimental cerebral edema. We have detected gammoxyn - the most prospective substance for further study as cere-broprotector. We have established that gammoxyn has a signified protective action in cerebral edema.